2014
DOI: 10.1007/s10342-014-0832-4
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation tolerance and cryopreservation of seeds of black poplar (Populus nigra L.), a disappearing tree species in Europe

Abstract: Black poplar (Populus nigra L.) is a widely distributed species that plays a crucial role in riparian forest ecosystems. Due to a reduction in its natural habitats and hybridization with introduced poplar species clones, its genetic pool is decreasing and efforts are required to preserve this species. Seeds of black poplar are short-lived and quickly lose viability during conventional storage in gene banks. Therefore, in order to preserve ex situ the genetic diversity of this species, the feasibility of seed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
(32 reference statements)
1
30
0
1
Order By: Relevance
“…2). (Ellis et al 1991a, b;Sacandé et al 2000;Hor et al 2005;Eira et al 2006;Pérez et al 2012); (2) seeds that exhibit anomalous longevity responses to temperatures between ?10 and -30°C (Ellis et al 1991a, b;Hor et al 2005;Eira et al 2006;Crane et al 2006;Pérez et al 2012); or (3) seeds that have short lifespans no matter how they are dried or cooled (Mondoni et al 2010;Michalak et al 2015). Water content thresholds and time for lethal damage to accumulate are cross-cutting parameters used to characterize all seed types.…”
Section: In-between Orthodox and Recalcitrant Seed Storage Categoriesmentioning
confidence: 99%
“…2). (Ellis et al 1991a, b;Sacandé et al 2000;Hor et al 2005;Eira et al 2006;Pérez et al 2012); (2) seeds that exhibit anomalous longevity responses to temperatures between ?10 and -30°C (Ellis et al 1991a, b;Hor et al 2005;Eira et al 2006;Crane et al 2006;Pérez et al 2012); or (3) seeds that have short lifespans no matter how they are dried or cooled (Mondoni et al 2010;Michalak et al 2015). Water content thresholds and time for lethal damage to accumulate are cross-cutting parameters used to characterize all seed types.…”
Section: In-between Orthodox and Recalcitrant Seed Storage Categoriesmentioning
confidence: 99%
“…Additionally, fresh seeds that were collected in 2012 were used as a control. Details of the storage protocols were described in Suszka et al (2014) and Michalak et al (2014).…”
Section: Plant Materialsmentioning
confidence: 99%
“…This requires the development of seed storage methods that can retain the ability of seeds to germinate after many years. Various seed storage temperatures have been reported for P. nigra, which have resulted in the ability to store the seeds for different lengths of time and still retain sufficient levels of seed viability (Stanton and Villar 1996;Tylkowski 2010;Michalak et al 2014;Suszka et al 2014). Thus far in the literature, optimal seed storage conditions have been assessed on the basis of seed germination (Popova et al 2012;Malik et al 2013;Suszka et al 2014) or seedling emergence (Michalak et al 2013;Popova et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Michalak et al (2015) also demonstrated that MC within 0.11-0.17 g g -1 plays an important role in the cryopreservation of black poplar seeds irrespective of its origin, time of harvesting and the seed quality.…”
Section: Influence Of Moisture Contentmentioning
confidence: 99%
“…The temperature was sustained at 23 o C and 27 o C for 22 h and 2 h per day, respectively. The use of Jacobsen germinator was also described in the reports of Chmielarz (2010) and Michalak et al (2015). As per their description, the seeds were thawed by keeping in a water bath at 40 o C for 5 min following LN exposure before transferring them in Jacobsen germinator.…”
Section: Post-cryopreservation Regrowthmentioning
confidence: 99%